The peasant image and agrarian change: representations of rural society in nineteenth‐century French painting from millet to van Gogh - Juneja, Monica (The journal of peasant studies, 1988)
In the upsurge of rustic themes in French painting during the second half of the nineteenth century is articulated a range of urban responses to agrarian and industrial transformation of country and city at the time. The recreation through art of ‘peasant culture’ was rooted in preoccupations about work and production, changing social relations and forms of sociability, the idea of the nation and the growth of political consciousness. This article examines some of the processes underlying the abundant production of peasant images ‐ the role of patronage, the growing importance of contemporary art criticism in formulating and diffusing values and sensibilities — as well as the complex and, at times, contradictory strains within the iconography of rural life in nineteenth‐century French art.